Promoting Diversity and Inclusion Through Multicultural Education in Classroom Settings - Meisuri Meisuri (Education Studies and Teaching Journal (EDUTECH), 2024)
This research aims to explore the role of multicultural education in fostering diversity and inclusion in the classroom environment. The research method used is systematic library observation with source identification from international databases such as ERIC, PsycINFO, Web of Science, and Scopus. The findings show that multicultural education has a crucial role in increasing understanding and appreciation of various cultures through activities such as storytelling and making crafts. In addition, multicultural education also increases empathy, tolerance, and respect among students, preparing them to become global citizens in an increasingly diverse world. In addition, attention also needs to be paid to research into how changes in educational policies and programs can support efforts to improve education through greater cultural diversity.